Potential of the Desert Locust Schistocerca gregaria (Orthoptera: Acrididae) as an Unconventional Source of Dietary and Therapeutic Sterols - Cheseto, Xavier; Kuate, Serge Philibert; Tchouassi, David P.; Ndung’u, Mary; Teal, Peter E. A.; Torto, Baldwyn (PLOS ONE, 2015)
Insects are increasingly being recognized not only as a source of food to feed the ever growing world population but also as potential sources of new products and therapeutic agents, among which are sterols. In this study, we sought to profile sterols and their derivatives present in the desert locust, Schistocerca gregaria, focusing on those with potential importance as dietary and therapeutic components for humans. Using coupled gas chromatography-mass spectrometry (GC-MS), we analyzed and compared the quantities of sterols in the different sections of the gut and tissues of the locust. In the gut, we identified 34 sterols which showed a patchy distribution, but with the highest composition in the foregut (55%) followed by midgut (31%) and hindgut (14%). Fed ad libitum on wheat seedlings, five sterols unique to the insect were detected. These sterols were identified as 7-dehydrocholesterol, desmosterol, fucosterol, (3β, 5α) cholesta-8, 14, 24-trien-3-ol, 4, 4-dimethyl, and (3β, 20R) cholesta-5, 24-dien-3, 20-diol with the first three having known health benefits in humans. Incubation of the fore-, mid- and hindgut with cholesterol-[4-13C] yielded eight derivatives, three of these were detected in the gut of the desert locust after it had consumed the vegetative diet but were not detected in the diet. Our study shows that the desert locust ingests phytosterols from a vegetative diet and, amplifies and metabolizes them into derivatives with potential salutary benefits and we discuss our findings in this context.